A cloud-based data acquisition device - Goh, Reuben Zhi Yu (Nanyang Technological University, 2023)
Singapore’s severe labour crisis, exacerbated by the recent COVID-19 pandemic, has resulted in a manpower shortage in the building maintenance industry. With this acute manpower shortage, building maintenance personnels are unable to constantly check on every system in the building. Hence, system breakdown occurs more frequently, this causes stress and inconvenience to the building occupants. This paper focuses on the buildings’ ability to be maintained and how new technology can help Singapore realize its aim of being a smart nation. Utilizing Internet of Things (IoT) technology in building maintenance systems can significantly minimize the need for labour-intensive manual work. Market research and surveys on the current IoT products and cloud solutions on the market have been done throughout the study. The study concluded that there was a lack of IoT devices on the market that could log data. It is crucial to gather data in our systems as AI and Big Data grow more common. As a result, a cloud-based data acquisition device is created for a building’s rooftop water system’s electrical control panel. Although there are still some modifications to be done, this device has been installed effectively. All things considered, cutting-edge technology and big data can assist Singapore in realizing its vision of a smart nation and addressing its labour shortages.